KELAYAKAN FINANSIAL DAN ANALISIS NILAI TAMBAH PADA PENGOLAHAN BIJI KAKAO KUPAS TANPA SANGRAI DI UD. HARTA SARI SELEMADEG TABANAN BALI - Rama Krishna, Putu Agung Sujud; Wrasiati, Luh Putu; Ganda Putra, G.P (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): Desember, 2018)
Peeled without roasting cocoa beans is a new product at UD. Harta Sari and still not so much (15%) of the total production per year of production . The purpose of the study is to, determine the financial feasibility of the peeled beans non roasting business , determine the value added of processing, and determine the business feasibility of peeled beans non roasting if there is an increase in operational costs and a decrease in income using sensitivity analysis . Financial feasibility analysis uses quantitative descriptive analysis using calculations profit and loss, Net Present Value, Internal Rate of Return, Net B/C Ratio, Payback Period, and Break Event Point, and Value added analysis using Hayami method. The results showed that financial feasibility analysis that is Net Present Value of Rp. 56,933,644. Internal Rate of Return of 5.49%. Payback Period for 3 year 10 months, and Net B/C Ratio of 1.32. It is based on added value obtained from the processing of peeled cocoa beans non roasting is Rp.  6,250/Kg. The business of peeled cocoa beans non roasting as a whole is profitable with a net profit of Rp. 78,231,000 of year and worth developing. Sensitivity analysis indicates that an increase in operational cost of 2.5% and a 1.5% revenue decrease does not affect the feasibility of the project. Based on the results of research on the business of peeled cocoa beans non roasting is feasible. Keywords : cocoa, financial feasibility, value added